2014
DOI: 10.1371/journal.pone.0094718
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid-Modified Magnetic Iron Oxide Nanoparticles for MR Imaging of Surgically Induced Endometriosis Model in Rats

Abstract: Endometriosis is defined as the presence of endometrial tissue outside the uterine, which may affect nearly 60% of women in reproductive age. Deep infiltrating endometriosis (DIE) defined as an endometriotic lesion penetrating into the retroperitoneal space or the wall of the pelvic organs to a depth of at least 5 mm represents the most diagnostic challenge. Herein, we reported the use of hyaluronic acid (HA)-modified magnetic iron oxide nanoparticles (HA-Fe3O4 NPs) for magnetic resonance (MR) imaging of endom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 41 publications
0
43
0
Order By: Relevance
“…[ 37 ] The similar biodistribution profiles of SiNc‐NP in mice with cancer and mice with endometriotic grafts following intravenous injection could be explained by the fact that both cancer and endometriosis are angiogenesis‐dependent diseases and the nanoparticles can accumulate in tumors and endometriotic lesions by extravasation through permeable blood vessels. [ 38,39 ] Angiogenesis represents a key factor in the growth and development of endometriotic lesions, and growing evidence in the primary literature supports a role for vascular endothelial growth factor in both the regulation of neovascularization and the increased permeability of endometriotic vascularity. [ 40 ] Immunostaining of the sectioned tissues with both Factor 8 (Figure 5D) and CD31 (Figure 6D,E) antibodies revealed the extensive vascular development in the endometriotic grafts used in our experiments that parallels angiogenesis in lesions in both macaques and women.…”
Section: Resultsmentioning
confidence: 99%
“…[ 37 ] The similar biodistribution profiles of SiNc‐NP in mice with cancer and mice with endometriotic grafts following intravenous injection could be explained by the fact that both cancer and endometriosis are angiogenesis‐dependent diseases and the nanoparticles can accumulate in tumors and endometriotic lesions by extravasation through permeable blood vessels. [ 38,39 ] Angiogenesis represents a key factor in the growth and development of endometriotic lesions, and growing evidence in the primary literature supports a role for vascular endothelial growth factor in both the regulation of neovascularization and the increased permeability of endometriotic vascularity. [ 40 ] Immunostaining of the sectioned tissues with both Factor 8 (Figure 5D) and CD31 (Figure 6D,E) antibodies revealed the extensive vascular development in the endometriotic grafts used in our experiments that parallels angiogenesis in lesions in both macaques and women.…”
Section: Resultsmentioning
confidence: 99%
“…Polyethyleneimine (PEI) is one of the more used ligands. 49 The same group 50,51 has reported that hyaluronic acid targeted iron oxide nanoparticles are efficient probes for targeted MRI of cancer cells in vitro and xenografted tumor model in vivo. Other types of ligands have been studied for the targeting of such markers including antibodies, small peptides, lectins, aptamers, engineered proteins, and protein fragments.…”
mentioning
confidence: 99%
“…110 Alternatively, magnetic oxide NPs, which had been modified with hyaluronic acid (HA-Fe 3 O 4 NPs), have shown potential in detecting lesions. 111 Investigations into the treatment of endometriosis have used the therapeutic gene, pigment epithelium-derived factor (PEDF), which has both antitumor and antiangiogenic properties. Lipid-grafted chitosan micelles were loaded with PEDF and intravenously injected into rats with surgically induced endometriosis.…”
Section: Reproductive Health Carementioning
confidence: 99%